2017
DOI: 10.35188/unu-wider/2017/329-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender identity and female labour supply in Brazil

Abstract: Over the last half-century, the role of women in society has changed substantially. However, the gender income gap and the difference in labour force participation persist. Akerlof and Kranton introduce the concept of identity from sociology and social psychology at the economic analysis; based on this we search less traditional factors for understanding this persistence. We extend the analysis proposed by Bertrand et al. for Brazil. Specifically, we analyse the impact of gender identity, focusing on the presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…However, replications of their study return mixed results. Codazzi et al (2017) confirmed that wives in Brazil distort their labor market outcomes to maintain gender identity conformity. Yet, no discontinuity in the wife's share of income is found for Sweden (Hederos Eriksson & Stenberg, 2015), Finland or the U.S. (Binder & Lam, 2018;Zinovyeva & Tverdostup, 2018) after accounting for heaping issues at the 50 percent threshold.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, replications of their study return mixed results. Codazzi et al (2017) confirmed that wives in Brazil distort their labor market outcomes to maintain gender identity conformity. Yet, no discontinuity in the wife's share of income is found for Sweden (Hederos Eriksson & Stenberg, 2015), Finland or the U.S. (Binder & Lam, 2018;Zinovyeva & Tverdostup, 2018) after accounting for heaping issues at the 50 percent threshold.…”
Section: Introductionmentioning
confidence: 78%
“…Second, we present evidence suggesting that the prevalence of male breadwinning as gender prescription is shaped by a country's institutional system. Studies using the discontinuity test (Bertrand et al, 2015;Binder & Lam, 2018;Hederos Eriksson & Stenberg, 2015;Codazzi et al, 2017;Zinovyeva & Tverdostup, 2018) cannot isolate cultural from institutional effects on female labor market outcomes, because gender identity prescriptions are analyzed within a given political and statutory framework. Therefore, differences in prescriptions between countries might be a result of country-specific cultures as well as of welfare state characteristics and public policy, where specific relationships are difficult to disentangle (Nyman, Reinikainen, & Stocks, 2013;Pfau-Effinger, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, replications of their study return mixed results. Codazzi et al (2017) confirmed that wives in Brazil distort their labor market outcomes to maintain gender identity conformity. Yet, no discontinuity in the wife's share of income is found for Sweden (Hederos Eriksson & Stenberg, 2015), Finland or the U.S. (Binder & Lam, 2018;Zinovyeva & Tverdostup, 2018) after accounting for heaping issues at the 50 percent threshold.…”
Section: Introductionmentioning
confidence: 78%
“…Second, we present evidence suggesting that the prevalence of male breadwinning as gender prescription is shaped by a country's institutional system. Studies using the discontinuity test (Bertrand et al, 2015;Binder & Lam, 2018;Hederos Eriksson & Stenberg, 2015;Codazzi et al, 2017;Zinovyeva & Tverdostup, 2018) cannot isolate cultural from institutional effects on female labor market outcomes, because gender identity prescriptions are analyzed within a given political and statutory framework. Therefore, differences in prescriptions between countries might be a result of country-specific cultures as well as of welfare state characteristics and public policy, where specific relationships are difficult to disentangle (Nyman, Reinikainen, & Stocks, 2013;Pfau-Effinger, 2012).…”
Section: Introductionmentioning
confidence: 99%